Forgiveness and Health: Review and Reflections on a Matter of Faith, Feelings, and Physiology - Vanoyen Witvliet, Charlotte (Journal of psychology and theology, 2001)
Empirical research on the links between forgiveness and both mental and physical health is burgeoning. This article reviews current research, with reflections on how Christians might engage this literature. It considers Christian and psychological conceptualizations of forgiveness, reviews the published literature on forgiveness and mental and physical health, addresses theoretical and interpretive issues, and reflects on ways that Christians may thoughtfully consider the contributions and limitations of empirical research on forgiveness and health.